1997
DOI: 10.1007/s002280050361
|View full text |Cite
|
Sign up to set email alerts
|

Asthma education for Swedish primary care physicians - a study on the effects of "academic detailing" on practice and patient knowledge

Abstract: The study shows differences between the intervention and control areas regarding the knowledge and practice of GPs after the intervention. We found changes in knowledge, attitudes and actual practice, the latter being measured by the prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…Tomson et al, study reported that there were changes in knowledge, attitudes and actual practice of Swedish primary care physicians after intervention messages concerning management of bronchial asthma. [11] A similar study by Rovithis et al, demonstrated an improvement in knowledge of PHC physicians serving a rural population on the island of Crete after a one-day educational course on bronchial asthma clinical guidelines. [8] These results stress the need for interventions in the form of frequent courses and continuing education to improve knowledge and practice of health care personnel about asthma and disease management.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Tomson et al, study reported that there were changes in knowledge, attitudes and actual practice of Swedish primary care physicians after intervention messages concerning management of bronchial asthma. [11] A similar study by Rovithis et al, demonstrated an improvement in knowledge of PHC physicians serving a rural population on the island of Crete after a one-day educational course on bronchial asthma clinical guidelines. [8] These results stress the need for interventions in the form of frequent courses and continuing education to improve knowledge and practice of health care personnel about asthma and disease management.…”
Section: Discussionmentioning
confidence: 76%
“…The results were in agreement with other studies among PHC physicians and nurses. [10,11,13,[15][16][17] A study of the level of knowledge about childhood asthma showed that general practitioners scored well in most questions but had some defi ciencies particularly in distinguishing preventive therapy from symptom-relieving medication. [10] Pediatric nurses in the previous study had poor knowledge of exerciseinduced asthma, which is similar to the result of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birçok ülkede bu hekim grubunun bilgi düzeylerini araştırmaya yönelik çalışmalar yapılmış ve ülkeler bazında hekimlerin farklı düzeylerde bilgiye sahip oldukları görülmüştür (18)(19)(20). Çalışmaların farklı tasarımları, farklı soruları içermeleri birbirleri ile karşılaştırma yapılmasına olanak sağlamıyor olsa da genel olarak her ülkede, birinci basamakta astım ve KOAH'lı hasta yönetiminde bilgi eksiklikleri olduğu söylenilebilir (18)(19)(20)(21). Birinci basamak hekimlerin uzmanlara göre solunum yolu hastalıklarına doğru tanı koyabilme oranlarının düşük olduğu (%42.4) özellikle vurgulanmıştır (22).…”
Section: Discussionunclassified
“…As a first step, we searched the literature for published studies and instruments to assess physician asthma knowledge. Although we found several studies addressing this issue, (9)(10)(11)(12)(13) their relevance was limited (i.e., based on earlier versions of guidelines or too narrow in scope).…”
Section: Instrument Developmentmentioning
confidence: 95%